VALIDATE: Exploiting the synergy between complex intracellular pathogens to expedite vaccine research and development for tuberculosis, leishmaniasis, melioidosis and leprosy [version 1; referees: 2 approved] - Helen A. Fletcher; Mitali Chatterjee; Andrea Cooper; Tracy Hussell; Paul M. Kaye; Joann Prior; Rajko Reljic; Samantha Vermaak; Martin Vordermeier; Ann Williams; Helen McShane (F1000Research, 2018)
For several complex intracellular pathogens, we have an urgent need for effective vaccines and yet there are common barriers to vaccine development. These diseases, including tuberculosis, leishmaniasis, leprosy and melioidosis, cause a huge burden of disease and disproportionately affect low and middle income countries. They are therefore often neglected due to the marginalisation of affected populations and the poor predicted commercial return on investment. Barriers to vaccine development include an incomplete understanding of protective immunity and translation from the bench into clinical vaccine trials. The current linear approach to vaccine research and development for these pathogens, which involves basic research, vaccine design, and vaccine evaluation in preclinical challenge models and clinical trials, is inefficient for these complex intracellular pathogens. We have established a Global Challenges Research Fund Network for VAccine deveLopment for complex Intracellular neglecteD pAThogEns, “VALIDATE”, where we aim to adopt a more flexible, integrated cross-pathogen approach to accelerate vaccine research and clinical development for these four pathogens, by cross-pathogen analyses, cross-discipline collaborations, and repeated integration of data from human and animal studies. This network provides a unique opportunity to bring together individuals working on four exemplar complex intracellular neglected pathogens (M.tb, Leishmania spp., B. pseudomallei and M.leprae), which share a common lifestyle as pathogens of macrophages, induce similar end-stage pathologies and alter host immune and metabolic responses. The horizontal collaborations established throughout this network, together with the provision of a protected environment for early data sharing, will exploit these biological synergies.  By interrogating mechanisms that lead from infection to disease, we will be able to develop common vaccine development strategies for these and other complex intracellular pathogens.